Disciplinary Behavior and Exemplary Teacher as Influencing Factors - Muslida, Delvia; Firman, Firman; Riska, Riska (Universitas Negeri Padang, 2020)
This research is based on the phenomenon that is happening related to the relationship between teacher role models with disciplinary behavior and the influence of role models on student disciplinary behavior. This research is quantitative with descriptive correlational research. The sample in this study replaced 272 students who were determined through a proportional stratified random sampling technique. The instruments used were the teacher’s exemplary questionnaire and student disciplinary behavior questionnaire. Besides that, the researcher also used a Likert scale model instrument with five alternative answers. Data analysis techniques using simple regression analysis. And the results of the study show the influence of teacher exemplary behavior on student disciplinary behavior at school.